Relationship of vitamin D deficiency and gestational diabetes mellitus in pregnant women - Mantoo, Azmat J.; Jahan, Azmat; Younus, Zohra; Hamid, Umer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Gestational diabetes mellitus (GDM) is a common metabolic disorder among pregnant women. It is important to be diagnosed and treated early to minimize complications for both the mother and the foetus. Recent studies found that deficiency of vitamin D is a risk factor for GDM and its supplementation may be helpful in prevention of GDM. Objectives were to assess vitamin D status in pregnant women with or without GDM and to find out the association between vitamin D deficiency and GDM. Methods: A total of 400 patients were included in the study, 200 pregnant women diagnosed with GDM and 200 normoglycemic pregnant women. Serum 25 (OH) vitamin D concentration in these women were compared. Results: Only 6.75% of women were found to have normal vitamin D levels, all others having either insufficiency 18.5% or deficiency 74.75%. In case group around 79% of women had vitamin D deficiency, 70.5% in control group. In case group around 14.5% of women had vitamin D insufficiency, 22.5% in control group. In both case and control group around 6.5% and 7% of women were within the normal range respectively. Mean vitamin D is 14.3 ng/ml in case group and 15.4 ng/ml in control group. Conclusion: Prevalence of vitamin D deficiency is alarmingly high in pregnant women in India and has become a re-emerging public health issue and needs to be addressed.